Significance of public space in the fragmented city: Designing strategies for urban opportunities in informal settlements of Buenos Aires city - Flavio Janches (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This article surveys the problem of urban marginalization by one of its more critical expressions in the contemporary city: the slums. The aim is to define an urban design strategy for the integration of those settlements as part of the city context, which enables to find solutions for the conflict improving these communities quality of life.
Keywords: O18; O54; N96; R1; 330; slum; marginality; stigma; integration; public space; quality of life